Analisis Konseling Behavioral dengan Teknik Behavior Contract terhadap Perilaku Terlambat Masuk Sekolah bagi Peserta Didik - Roni Sikapang; Surya Stefani; Jumiati Anton Lapu (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
The number of students arriving late often disrupts the classroom atmosphere and disrupts adherence to school rules. This study aims to assess the effectiveness of the behavioral contract technique in changing this habit. Using a qualitative approach focused on literature review, this study found that internal factors within students and environmental factors are the main causes of their tardiness. Behavioral counseling can help change behavior through reinforcement and habit training, while the behavioral contract technique provides clear rules and agreements that make students more responsible. Behavioral changes occur gradually and are more effective if students are involved and there is a balance between rewards and punishments. Therefore, this technique is suitable for use as a practical way to train student discipline in the school environment.